Project management - Field, Mike.; Keller, Laurie (London : Thomson Learning, 1998)
This book is divided into seven parts: Project initiation; Risk, estimates, and contracts; Planning; Building and leading the team; managing and controlling progress and cost; Managing quality and change; and Closing the project.
Keywords: Management; Industrial project management